FORMULATION AND EFFICACY TESTING OF SPF (Sun Protecting Factor) SUNSCREEN GEL EXTRACT OF RAMBUSA LEAVES (Passiflora Foetida L) - Fauziyyah Al Hasanah; Muthi’ah Rabbaniyyah; Eni Kurniati (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
The rambusa plant contains flavonoid compounds found in rambusa leaves which are good antioxidants because they have hydroxyl groups attached to aromatic carbon rings. This makes rambusa leaves able to ward off free radicals. The choice of gel composition is based on practical considerations because gel not only provides effective protection against sunlight but also has non-sticky properties, provides a soft feel and forms a film that adheres well to the skin. This research aims to determine the flavonoid content in rambusa leaves, which are antioxidants that can be formulated into sunscreen gel preparations to help protect the skin from sunlight. Determination of antioxidant levels in sunscreen gel preparations made from rambusa leaf extract was carried out by measuring the SPF (Sun Protection Factor) value at three different concentrations, namely 2%, 4%, and 6% using UV-Vis spectroscopy. The research results showed that all formulas had good physical quality values of the gel preparations. All formulas have varying SPF values, where the 2% concentration has maximum protection with an SPF value of 11.7 and the 4% and 6% concentrations have ultra protection with SPF values of 18.8 and 33.9. The conclusion of this research is that rambusa leaf extract has the potential to be an effective natural ingredient in sunscreen preparations and shows the ability to protect the skin from sunlight, where formulation 3 only has the highest SPF number, namely 33.90 (super protection). Keywords: Rambusa leaves, Protection, Sunscreen, SPF